Information needs and seeking behavior of male juvenile delinquents in Malaysian correctional schools / Ezza Rafedziawati Kamal Rafedzi - Ezza Rafedziawati , Kamal Rafedzi (2016)
Juvenile delinquents are marginalized populations as they live in small worlds of culture, which are very different from each other. Although their lives are different from the people outside the prison, they are also like other people who need support and guidance from outside society in education, career and social. The increased numbers of social deviance among adolescents in Malaysia have caused many young people to waste their time in prison. In the Malaysian context, young inmates are entitled to formal education and will be allowed to sit for public examinations under a special program under the Ministry of Education, in collaboration with the Prisons Department. The existence of the academic classes indirectly encourages young prisoners to use the various information sources and the prison library to obtain information related to their cultural, educational and social needs. Some scholars have been conducted juvenile delinquents research, but their research is highlighted to juvenile delinquency psychology, safety, criminal convictions and their family background. In this research, it is specifically to understand the information needs and seeking behavior among juvenile delinquents. Four (4) issues raised in this research : What are the information needs of male juvenile delinquents? How do male juvenile delinquents seek information in the prison environment? How does the prison environment support the male juvenile education and rehabilitation process? And what are the barriers to access the information needed by juvenile delinquents? Therefore, to fill in this research gap, the objectives of this study are; to understand the information needs and seeking behaviour of male juvenile delinquents and to explore how the prison information environment supports the information needs and seeking behaviour of the male juvenile delinquents. The research takes the form of a qualitative enquiry to establish what information was available for male juveniles in prison and what more could be made available. Quota sampling is employed in the selection of male juveniles based on the criteria that set up by the researcher. This study involves interpretive field interviewing of twenty three (23) selected participants from a population of 2,010 male juvenile delinquents and interpretive field observation of thirty two (32) participants from five (5) Correctional Schools under the jurisdiction of Malaysian Prison Department. The study obtained the legal consent from the Prison Policy Unit, Malaysian Prison Department, and the researcher had been investigate by the Ministry of Home Affairs before being allowed to make research in prison environment. The male juveniles as research participants; who met at least one of the criteria in the purposive sampling were sampled. Trustworthiness of data was assured through triangulation, member check, as well as audit trail, and researcher’s bias and assumptions are declared in the study. The main finding in this research is male juvenile delinquents need eight (8) importance information during their life in prison. The day-to-day information was the most important for the purpose of their safety and mutual support and information on prison operations for the purpose of their daily comfort.The study of information needs and information behavior among inmates will contribute to the use and improvement of the prison information environment, especially the prison library services. This will also facilitate the development of policies and practices to help inmates experiencing everyday information problems.